Towards a smart and data-driven campus: digital ecosystem development and the UiTM Johor RSP16 experience - Zainuddin, Noor Azrin; Mohd Rick, Abd Malik (Universiti Teknologi MARA, Johor, 2025)
As global institutions transition into the digital age, universities are redefining themselves to meet future challenges. A Smart Campus integrates digital tools, platforms, and data systems to provide seamless experiences for students, faculty, and administrators. UiTM Johor has embraced this transformation through RSP16—a flagship initiative aimed at modernising infrastructure, improving digital literacy, and fostering innovation. Central to this approach is the development of a Data Analytics Task Force and a Data War Room to support evidence-based governance and campus-wide performance monitoring.